STRATEGI DIPLOMASI EKONOMI INDONESIA DALAM WORLD CONFERENCE ON CREATIVE ECONOMY (WCCE) 2018–2023 - Rohaniah, Yoyoh; Pertiwanggono, Benny; Larasati, Diva Andhina (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The growth of the creative economy has had a significant impact on Indonesia’s national development since 2015. Recognizing its vast potential, President Joko Widodo and the Indonesian government identified the creative economy as a strategic sector with the capacity to position Indonesia as a global leader in this field by 2030. In pursuit of this vision, Indonesia initiated the first-ever international conference on the creative economy—the World Conference on Creative Economy (WCCE)—in 2018. This conference aimed to strengthen global collaboration and promote creative industries on a multilateral platform. WCCE also served as a channel for Indonesia’s economic diplomacy, designed to expand international cooperation, market access, and institutional partnerships for the creative economy sector. Through various diplomatic initiatives embedded in WCCE, the Indonesian government has contributed to strengthening bilateral relations, fostering policy innovation, and enhancing support mechanisms for creative economy actors. This research aims to analyze Indonesia’s economic diplomacy practices within the framework of WCCE from 2018 to 2023. Employing a qualitative descriptive method based on document analysis, the study explores the policy instruments and international engagements mobilized to achieve Indonesia’s aspiration to become a global creative economy hub.